Limited Nitrogen and Plant Growth Stages Discriminate Well Nitrogen Use, Uptake and Utilization Efficiency in Popcorn - Shahid Khan; Antônio Teixeira do Amaral Júnior; Fernando Rafael Alves Ferreira; Samuel Henrique Kamphorst; Gabriel Moreno Bernardo Gonçalves; Marta Simone Mendonça Freitas; Vanildo Silveira; Gonçalo Apolinário de Souza Filho; José Francisco Teixeira do Amaral; Ricardo Enrique Bresssan Smith; Iftikhar Hussain Khalil; Janieli Maganha Silva Vivas; et al. (Plants, 2020)
The extensive use of nitrogen (N) in agriculture has caused negative impacts on the environment and costs. In this context, two pot experiments were performed under different N levels and harvested at different vegetative stages to assess two popcorn inbred lines (P2 and L80) and their hybrid (F1 = P2 × L80) for the N use, uptake and utilization efficiency (with the inclusion and exclusion of root N content); to find the contrasting N levels and vegetative stages that effect nitrogen use efficiency (NUE) and to understand the relationship between the traits related to NUE. The hybrid and P2 were confirmed better than L80 for all the studied traits. NUE is mainly affected by the shoot dry weight, uptake and utilization efficiency. Extremely low and high N levels were found to be more discriminating for N use and dry weight, respectively. At the V6 (six fully expanded leaf) stage, root N content (RNC) should be considered; in contrast, at the VT (tasseling stage) stage, RNC should not be considered for the uptake and utilization efficiency. The genetic parameter performance for N use, uptake, shoot dry weight and N content could favor the achievement of the genetic gain in advanced segregating generations.